AN ANALYSIS OF STUDENTS PERCEPTION ON ENGLISH LEARNING VIA ZOOM CLOUD MEETING AT SMP AL-HIDAYAH MALANG. - RITA KRISMONIKA (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Zoom cloud meetings is one of the famous online learning platforms. It is an online meeting application with the concept of screen sharing. Not only on a PC or laptop, it can also be downloaded through a smartphone. The use of Zoom cloud meeting can support and ease the English learning process both teachers and students. However, the students’ perceptions of using Zoom Cloud Meeting on English learning are different in terms of the affordability of the gadget, the unfriendly interface, and signal conditions. So, the study is aimed to know the students perception on English learning via zoom cloud meeting at SMP Al-Hidayah Malang.     The researchers used descriptive qualitative research. The populations of the research were the students of SMP Al-Hidayah Malang. The researcher used the sample of the students from nine A Class. The samples were chosen by convenience sampling. The instruments of this study were questionnaire and interview. The questionnaire which was used in this study aimed to describe the students' perceptions about using Zoom Cloud Meetings on English learning in the midst of the Covid-19 pandemic. Meanwhile, the interview is guideline used to follow up the result from the questionnaire and provide more detailed information.     The results of the study showed that most students had positive perceptions or agreed to use Zoom Cloud Meeting in online English learning activities for several aspects, such as frequency of use, complexity, or ease of use, also practice using Zoom Cloud Meeting application. Most students enjoy learning English during online learning so that students can improve their English skills. While some of the students said that during the online learning of English through Zoom Cloud Meeting, it did not work as expected. Students said that online English Learning was not effective because of the difficulties they encountered such as unstable network or bed signal and less interaction. The conclusion of study showed that the researchers concluded that most students had positive perceptions or agreed to use Zoom Cloud Meeting in online English Learning but some students are not comfortable using zoom meeting because it is constrained by the network.